Natural language processing based clinical decision support - Lam, Yik Hong (Nanyang Technological University, 2024)
This project aims to research and develop a language model based system which extracts data from unstructured medical text into a structured format using locally run open-sourced resources. By developing such a model, the feasibility of medical institutions developing their own language models using their own medical data can be evaluated and assessed for potential future implementations especially with the expectations of further advancements in the domain of language models.